Autism spectrum disorder associated with 49, XYYYY: case report and review of the literature. Issue 1 (December 2017) - Demily, Caroline; Poisson, Alice; Peyroux, Elodie; Gatellier, Valérie; Nicolas, Alain; Rigard, Caroline; Schluth-Bolard, Caroline; Sanlaville, Damien; Rossi, Massimiliano
Abstract Background Sex chromosome aneuploidies occur in approximately one in 420 live births. The most frequent abnormalities are 45, X (Turner syndrome), 47, XXX (triple X), 47, XXY (Klinefelter syndrome), and 47, XYY. The prevalence of males with more than one extra sex chromosome (e.g. 48, XXYY or 48, XXXY) is less common. However, the literature provides little information about the cognitive and behavioural phenotype and the natural history of the disease. We report the clinical, neurocognitive, social cognitive and psychiatric characterization of a patient with 49, XYYYY syndrome. Case presentation The patient presented with a complex phenotype including a particular cognitive profile with intellectual deficiency and autism spectrum disorder (ASD) with limited interests. Moreover, social anxiety disorder with selective mutism and separation anxiety disorder were observed (DSM-5 criteria, MINI Assessment). Conclusion It is now admitted that 49, XYYYY has unique medical, neurodevelopmental and behavioural characteristics. Interestingly, ASD is more common in groups with Y chromosome aneuploidy. This clinical report suggests that understanding the cognitive and social functioning of these patients may provide new insights into possible therapeutic strategies, as cognitive remediation or social cognitive training.